Impact of The COVID-19 Pandemic on Salivary Gland-related Healthcare Interventions; A Systematic Review And Meta-analysis - Kiran, Myle Akshay; Saeed, Safa; Bin Nafisah , Abeer; Alqarni, Abdulaziz; Haif Alotaibi, Atheer; Saleh Alqahtani , Abdulaziz; Aljadaan , Hend; Bin Osayl , Haya; Alsane, Maha; Alsuhail, Norah; et al. (Galen Medical Journal, 2025)
Abstract Background: The emergence of SARS-CoV-2 variants has raised concerns regarding their potential impact on perioperative outcomes. Its effect on patients undergoing surgery for salivary gland diseases remains unclear. This systematic review and meta-analysis aimed to evaluate the impact of the COVID-19 pandemic on salivary gland-related healthcare interventions, including cancer treatments, sialendoscopy procedures, and parotid surgery outcomes. Materials and Methods: Following PRISMA guidelines, a systematic search was conducted in PubMed, Embase, and Web of Science (2019–2025) for studies reporting pre- and during-COVID data. Two reviewers independently screened records, extracted data, and assessed risk of bias using the Newcastle-Ottawa Scale. A random-effects meta-analysis was performed to pool odds ratios (ORs) for intervention outcomes. Results: Four studies (n=7,740 participants) were included. The pooled OR for salivary gland interventions during versus pre-COVID was 1.08 (95% CI: 0.88–1.33, P=0.45), indicating no significant change, with moderate heterogeneity (I²=46%). Subgroup analyses revealed increased odds of wound dehiscence post-parotid surgery (OR=4.40, 95% CI: 1.18–16.40) but no significant differences in delayed cancer diagnosis or urgent sialendoscopy. Conclusion: The COVID-19 pandemic did not significantly alter overall salivary gland intervention rates or adverse events, though some procedural complications increased non-significantly. Limited evidence underscores the need for larger, standardized studies. While this shows that surgeons maintained quality of practice in this era during the COVID-19.